Trabalhadores e trabalhadoras da saúde: acidentes, uso de equipamentos de proteção individual e produtividade - Gonzaga, Sandro Lopes (2023)
Healthcare workers are constantly at risk of occupational accidents involving exposure to biological material. Although the causes are diverse, two stand out for their recurrence and difficulty in resolution: inadequate use of personal protective equipment (PPE) and work overload related to increased productivity. This study aimed to understand the use of PPE by healthcare professionals to prevent biological accidents and to analyze the influence of healthcare institutions productivity on the occurrence of such accidents. The methodology consisted of: (1) an integrative review of articles published in the Virtual Health Library (BVS) on the use of PPE in healthcare institutions; and (2) a quantitative research to verify the influence of productivity on the occurrence of biological accidents. The results showed that: (1), the first article identified flaws in the use of PPE by healthcare professionals; and (2) the second article was able to identify the influence of increased productivity on the occurrence of accidents. Therefore, it is concluded, that the elimination of biological accidents requires measure that address all their causes, especially the most recurrent and difficult ones. Among other measures, we suggest more appropriate human resources management, improvement of work organization, and improvement of PPE use management.